INDONESIA ISLAMIC BANK PROFITABILITY 2010-2017 - Nugroho, Lucky; Badawi, Ahmad; Hidayah, Nurul (IAIN Surakarta, 2019)
This study proposes to determine the board management structure, bad debt, and efficiency of the profitability of the Islamic banks during 2007-2017 period. The quantitative data has been analyzed by using multiple regression analysis to determine the effect of independent variables on the variable dependent. Furthermore, the statistic tools used in the data process is Stata version 13. This study shows that the board of directors of the parent bank has a negative and significant influence on profitability. The problem financing has a negative and significant effect on profitability. Likewise, the ratio of operational costs also has a negative and significant effect on profitability. Thus, the existence of a parent bank's board of management to improve the performance of Islamic banks needs to be considered because it has not been able to provide an optimal contribution. In addition, the significant amount of financing quality and the use of inefficient operational costs have been a problem of improving profits from Islamic banks. Keywords: parent bank, bad debt, efficiency, profitability, Islamic banks